Democratization in Taiwan : implications for China - Tien, Hung-mao; Tsang, Steve Yui-Sang (St. Antony's series (Macmillan), 1999)
Democratization in Taiwan from the late 1980s to the late 1990s raises the question of whether a similar process can happen in China, and dispels the old conception that democratization is incompatible with the Chinese/Confucian tradition. This volume examines the nature of and the dynamics in the democratization of a Leninist style party state in Taiwan and its implications for China still governed under a Leninist system. It also assesses the process of democratic consolidation and the political, military and diplomatic reality which constrains democratization in Taiwan